2009
DOI: 10.1098/rsbl.2009.0123
|View full text |Cite
|
Sign up to set email alerts
|

Methane emission by plant communities in an alpine meadow on the Qinghai-Tibetan Plateau: a new experimental study of alpine meadows and oat pasture

Abstract: Recently, plant-derived methane (CH 4 ) emission has been questioned because limited evidence of the chemical mechanism has been identified to account for the process. We conducted an experiment with four treatments (i.e. winter-grazed, natural alpine meadow; naturally restored alpine meadow eight years after cultivation; oat pasture and bare soil without roots) during the growing seasons of 2007 and 2008 to examine the question of CH 4 emission by plant communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 21 publications
(39 reference statements)
0
18
0
1
Order By: Relevance
“…soil or plant water) and whether plants have their own mechanism(s) to produce CH 4 have been debated (Bruhn et al, 2012;Keppler et al, 2009;Nisbet et al, 2009). Evidence is now accumulating to indicate that plants can produce CH 4 even in the presence of oxygen (Bruggemann et al, 2009;Bruhn et al, 2009Bruhn et al, , 2014Cao et al, 2008;Fraser et al, 2015;Keppler et al, 2008;Lenhart et al, 2014;McLeod et al, 2008;Messenger et al, 2009;Mikkelsen et al, 2011;Reid, 2009, 2011;Sanhueza and Donoso, 2006;Sinha et al, 2007;Vigano et al, 2009Vigano et al, , 2008Wang et al, 2009aWang et al, , 2009bWang et al, , 2011aWatanabe et al, 2012;Wishkerman et al, 2011).…”
Section: Plantsmentioning
confidence: 99%
“…soil or plant water) and whether plants have their own mechanism(s) to produce CH 4 have been debated (Bruhn et al, 2012;Keppler et al, 2009;Nisbet et al, 2009). Evidence is now accumulating to indicate that plants can produce CH 4 even in the presence of oxygen (Bruggemann et al, 2009;Bruhn et al, 2009Bruhn et al, , 2014Cao et al, 2008;Fraser et al, 2015;Keppler et al, 2008;Lenhart et al, 2014;McLeod et al, 2008;Messenger et al, 2009;Mikkelsen et al, 2011;Reid, 2009, 2011;Sanhueza and Donoso, 2006;Sinha et al, 2007;Vigano et al, 2009Vigano et al, , 2008Wang et al, 2009aWang et al, , 2009bWang et al, , 2011aWatanabe et al, 2012;Wishkerman et al, 2011).…”
Section: Plantsmentioning
confidence: 99%
“…During the past decades, many studies concerned about CH 4 fluxes from grasslands, with several reports indicating CH 4 emissions from wet meadows (Cao et al, 2008;Wang et al, 2009b;Chen et al, 2011;Liu et al, 2012a). Based on analyses of data taken from 50 articles (including several theses, , which is comparable with CH 4 uptake rates from other grasslands in the world (Mosier et al, 1991;Glatzel and Stahr, 2001;Mosier et al, 2002;Mori et al, 2008;Castaldi et al, 2010;Merbold et al, 2013).…”
Section: Observed Ch 4 Uptakes In Grasslands In Chinamentioning
confidence: 99%
“…So far to the best of our knowledge, there is no synthesis study on a comprehensive CH 4 budget for either grasslands or forests in China, which is indispensable for a general CH 4 uptake estimate for this country. Multiple studies on CH 4 fluxes of grasslands in China have already been carried out Wang et al, 1998Wang et al, , 2000Wang et al, , 2005Wang et al, , 2007Wang et al, , 2009bDong et al, 2000Dong et al, , 2005Ma et al, 2006;Li et al, 2007;Liu et al, 2007Liu et al, , 2011Liu et al, , 2012aHolst et al, 2008;Sun, 2008;Chen et al, 2010;Geng et al, 2010;Zhou et al, 2011;Luo and Jiao, 2012;Wei et al, 2012;Zhang et al, 2012), some even making efforts to estimate the total emission for specific regions Liu et al, 2009a;Wang et al, 2009c). Relatively fewer studies on CH 4 fluxes of forests in China have been published (Xu et al, 1995;Sun, 2000;Dong et al, 2003;Du et al, 2004;Mo et al, 2005;Yang et al, 2010;Liu et al, 2010bLiu et al, , 2012bGuan et al, 2012;Yang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cincotta et al (1992) argued that plant-herbivore interaction is the driving force of plant population dynamics on the eastern part of the Tibetan plateau, while Dorji et al (2010) indicated that climatic variability is the principle driver of plant community properties on the northwestern part of the Tibetan plateau. While research has been conducted at large scales across the Tibetan Plateau (Shimono et al, 2010) and within experimental plots (Klein et al, 2004;Wang et al, 2009;Dorji et al, 2013b), there has been less work at an intermediate scale on how plant community properties may be controlled by abiotic environmental conditions and grazing intensity. Moreover, most plant ecological studies on the Tibetan Plateau are located on its eastern margin, and there is little information regarding plant community properties in the central Tibet grasslands.…”
Section: Introductionmentioning
confidence: 99%